Systematic remarks on eriophyoid mites from the subfamily Phytoptinae Murray, 1877 (Acari: Eriophyoidea: Phytoptidae) - Chetverikov, Philipp E.; Petanović, Radmila U.; Sukhareva, Sogdiana I. (Zootaxa, 2009)
In this paper a critical analysis of the subfamily Phytoptinae is undertaken. Five new combinations are stated: Oziella nilotica (Abou-Awad, 1981) comb. n. (from Phytopus Dujardin, 1851); O. gigantica (Mohanasundaram, 1981) comb. n. (from Anchiphytoptus Keifer, 1952); Phytoptus lineatus (Keifer, 1952) comb. n., Ph. beeri (Keifer, 1957) comb. n. and Ph. chamaebatiae (Keifer, 1975) comb. n. (all of them from Anchiphytoptus Keifer, 1952). The genus Anchiphytoptus Keifer, 1952 is considered to be a junior synonym of Phytoptus Dujardin, 1851.